Thermal case study of magnetic radiative flow impacts on Newtonian nanofluid over a stretchable plate in absorbent: box approach - Hussain, Syed M.; E Shams, Zill; Rubbab, Qammar; Mohd Nasir, Nor Ain Azeany; Abd-Elmonem, Assmaa; Elmki Abdalla, Nesreen Sirelkhtam; Qureshi, Muhammad Amer; Ahmad, Hijaz (Elsevier, 2024)
Nanofluid technology represents a significant breakthrough in thermal engineering, with widespread applications spanning heat exchangers, cancer treatment, and heat storage systems. Despite its success in improving heat transfer rates in diverse devices, the challenge of enhancing thermal conductivity using nanoparticles looms large. This study aims to elucidate the 2D flow of nanofluid under suction/injection over a stretching wedge. It considers factors such as Brownian and thermophoretic diffusions, nonlinear heat generation, and thermal radiation. Additionally, it examines the effects of viscous dissipation and Joule heating. Through the conversion of governing nonlinear coupled partial differential equations into a system of coupled ordinary differential equations using similarity transformations, numerical solutions are obtained via the Keller-box method. The analysis delves into the significant impacts of relevant parameters on velocity, temperature, concentration, and microorganism fields, presented graphically. Notably, the findings underscore the role of solid particles in enhancing the thermal efficiency of base fluids. These investigation outcomes are vital for controlling heat transferal rates and fluid velocities throughout a variation of manufacturing processes and industrial sectors, guaranteeing the required quality of the ending product. The perceptions garnered from this research hold capacity for a broad range of industrial purposes and carry consequences through countless engineering disciplines, mostly within the range of nanotechnology.